Teacher Exhaustion during COVID-19: Exploring the Role of Administrators, Self-Efficacy, and Anxiety. Issue 1 (2nd January 2022) - Pressley, Tim; Ha, Cheyeon
Abstract: This study aimed to understand the relationships among administrative support, teacher self-efficacy, and teacher anxiety on teacher stress during COVID-19. The study explored United States teacher perceptions during Fall 2020 as teachers and schools returned to teaching in multiple online formats (hybrid and virtual). Teachers ( N  = 311) representing 16 states completed an electronic survey the first week of October 2020. To explain teachers' stress during the COVID-19 pandemic period and based on previous literature, we developed an SEM model with the variables of engagement and instructional efficacy, teaching anxiety, school administrator support, and teacher stress. The path model showed that teachers' psychological variables and administrative support were related to teachers' stress. In the final SEM model, the path results showed the complex indirect effects of teacher efficacy between the school administrative support and teachers' stress. The current results can guide schools in supporting teacher stress during an unprecedented time.